Racial issues in the works of Nella Larsen - Libnar, Petr (Univerzita Pardubice, 2024)
This diploma thesis deals with racial issues in the works of Nella Larsen. The theoretical part of the thesis is focused on topics such as Cultural Identity and African American Identity, and these terms are defined and explained in a broader context. Subsequently, the theoretical part of the thesis focuses on the major representatives of the African American ethnicity who actively participated in the formation of African American identity in the United States in the 20th century. Important concepts such as Pan-African Socialism, Old Negro, and New Negro are defined in this part of the thesis. The practical part of the thesis analyses the literary works of Nella Larsen, specifically the novel Passing and the short stories The Wrong Man, Freedom, and Sanctuary. These works are analysed in terms of racial inequality and the search for identity.
Rasová problematika v díle Nelly Larsonové
Keywords: Larsonová, Nella; rasová problematika; Afroameričané; identita; Passing; Larsen, Nella; racial issues; African American; identity; Passing